Molecular mining of alleles in water buffalo Bubalus bubalis and characterization of the TSPY1 and COL6A1 genes. - Sudeep Kumar; Ruchi Gupta; Sudhir Kumar; Sher Ali (PLoS ONE, 2011)
BACKGROUND: Minisatellites are an integral part of eukaryotic genomes and show variation in the complexity of their organization. Besides their presence in non-coding regions, a small fraction of them are part of the transcriptome, possibly participating in gene regulation, expression and silencing. We studied the minisatellite (TGG)(n) tagged transcriptome in the water buffalo Bubalus bubalis across various tissues and the spermatozoa, and characterized the genes TSPY1 and COL6A1 discovered in the process. RESULTS: Minisatellite associated sequence amplification (MASA) conducted using cDNA and oligonucleotide primer (TGG)(5) uncovered 38 different mRNA transcripts from somatic tissues and gonads and 15 from spermatozoa. These mRNA transcripts corresponded to several known and novel genes. The majority of the transcripts showed the highest level of expression either in the testes or spermatozoa with exception of a few showing higher expression levels in the lungs and liver. Transcript SR1, which is expressed in all the somatic tissues and gonads, was found to be similar to the Bos taurus collagen type VI alpha 1 gene (COL6A1). Similarly, SR29, a testis-specific transcript, was found to be similar to the Bos taurus testis-specific Y-encoded protein-1 representing cancer/testis antigen 78 (CT78). Subsequently, full length coding sequences (cds) of these two transcripts were obtained. Quantitative PCR (q-PCR) revealed 182-202 copies of the TSPY1 gene in water buffalo, which localized to the Y chromosome. CONCLUSIONS: The MASA approach enabled us to identify several genes, including two of clinical significance, without screening an entire cDNA library. Genes identified with TGG repeats are not part of a specific family of proteins and instead are distributed randomly throughout the genome. Genes showing elevated expression in the testes and spermatozoa may prove to be potential candidates for in-depth characterization. Furthermore, their possible involvement in fertility or lack thereof would augment animal biotechnology.